Keputusan Menggunakan Jasa Bengkel Mobil di Kabupaten Manokwari: Peran Kualitas Layanan, Faktor Individual, dan Lingkungan - Louis Soemadi Bopeng (Jurnal Ilmu Manajemen, 2021)
The workshop business in Manokwari has a phenomenon or a tendency for consumers or motorized vehicle owners to be disappointed when using the service of a repair shop because it does not match their expectations. The purpose of this study based on the formulation of the problem above is to determine the effect of service quality factors, individual factors, environmental factors on purchasing decisions. Also, the dominant factor influences. A sample of 118 respondents with the criteria of owning a four-wheeled motorized vehicle or more and having used a repair shop to maintain or repair their vehicle. The data collection method in this study is a survey method using a structured questionnaire. The data analysis method used is descriptive statistical methods and inferential statistical methods. An interesting finding from this study is that the results of the study prove that the factors that have the greatest influence on consumer purchasing decisions are environmental factors. This is considered rational for researchers because of the high sense of solidarity and concern among the Manokwari people plays an important role in their purchasing decision making. Opinions from friends become the main reference in making repair shop service decisions because they assume that Terman or the reference group has visited the workshop and they think the workshop is able to meet their expectations. Therefore, with a reference from a friend, they no longer experience confusion and spend time and money deciding which workshop to visit to purchase repair shop services.